Unfortunately, the browser used by Answers.com for posting questions is incapable of accepting mathematical symbols. This means that we cannot see the mathematically critical parts of the question. We are, therefore unable to determine what exactly the question is about and so cannot give a proper answer to your question.
3x2 + 2x + 2 = 0 Can not be factored. You can however solve it for x: 3x2 + 2x = -2 x2 + 2x/3 = -2/3 x2 + 2x/3 + 1/9 = -2/3 + 1/9 (x + 1/9)2 = -5/9 x + 1/9 = ±√(-5/9) x = -1/9 ± i√(5/9) x = -1/9 ± i√5 / 3 x = -1/9 ± 3i√5 / 9 x = (-1 ± 3i√5) / 9
2x+3=x+5Since x contains the variable to solve for, move it to the left-hand side of the equation by subtracting x from both sides.2x+3-x=5Since 2x and -x are like terms, add -x to 2x to get x.x+3=5Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides.x=-3+5Add 5 to -3 to get 2.x=2
2x + 7 = 1 Therefore, 2x = -6 x = -6/2 x = -3
x + 2x = 33 3x = 33 3x/3 = 33/3 x = 11
3x-2 = 2x+3 3x-2x = 3+2 x = 5
2x+3=9 x
2x - 3= 9 x=
2x + 3= 9.X=
Please help me solve this 2x + 3 = 9 x =. x=3 because 2x3=6+3=9
2x-3=9 so 2x=12 and x=6
2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!
x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3
2x + 3 = 9. What you need to do first, is to isolate the 'x' by itself. Subtract the 3 to the other side. 2x + 3 = 9. (Before subtraction) 2x = 6 (After subtraction) Then you can divide by whatever is on the 'x'. In this case, it is 2. (Before) 2x = 6 (After) x = 3. Now you can check the problem, so put in 3 for x. 2x + 3 = 9. 2(3) + 3 = 9. 6 + 3 = 9. 9 = 9.
-9-2x=9-8x6x=18 x=3
3/2x = 9 Multiply both sides by 2x: 3 = 18x Divide both sides by 18: 1/6 = x, that is x = 1/6 = 0.166...
2x+3=9x 3=9x-2x 3=7x x=3/7
2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3